أساليب التنشئة الأسرية وعلاقتها بمركز الضبط لدى عينة من طلبة الأول الثانوي العام في مدارس مدينة دمشق الرسمية - الزعبي, أحمد; العبد الله, فايزة غازي (Latakia University Journal - Arts and Humanities Sciences Series, 2013)
يهدف البحث إلى معرفة العلاقة بين أساليب التنشئة الأسرية ومركز الضبط لدى عينة من طلبة الصف الأول الثانوي العام في مدارس مدينة دمشق الثانوية الرسمية ، وتحديد فيما إذا كانت هناك فروق بين الذكور والإناث في أساليب التنشئة الأسرية من جهة ، ومن جهة أخرى معرفة الفروق في مركز الضبط تبعاً لمتغير الجنس ، وقد تكونت عينة البحث من (372) طالباً وطالبة منهم (183) طالباً، وتكونت عينة الإناث و من (189) طالبة، اختيروا بطريقة عشوائية طبقية بسيطة، وقد طبق عليهم اختبار التنشئة الأسرية واختبار مركز الضبط لروتر، وتوصل البحث إلى عدد من النتائج يمكن تلخيصها بما يلي: - وجود علاقة ارتباطيه دالة إحصائياً بين عدد من أساليب التنشئة الأسرية منها أسلوب الاستقلال ومركز الضبط، وأسلوب التقبل ومركز الضبط، كما تبين بأن أسلوب الحماية الزائدة أدى إلى مركز ضبط منخفض - كما أظهرت النتائج وجود فروق ذات دلالة إحصائية بين الذكور والإناث في أسلوب الاستقلال لصالح الذكور، ووجود فروق بين الذكور والإناث في أسلوب الحماية لصالح الإناث. The current study aims to discover the relationship between the patterns of family upbringing and the control center for a sample of first year high school students at public high schools. It also aims to determine whether there are any differences between females and males in methods of family upbringing on the one hand and knowing these differences in the control center based on the gender variable. In order to achieve the goal of this study, a sample of 372 students (183 male students – 189 female students) was selected randomly from the first year high school at public schools in the city of Damascus. They underwent the family upbringing test and Router's local control center test. The study has yielded a number of results, the most important of which are: - There is a connective relationship of statistical indication among a number of family upbringing patters such as the independency and local control pattern, the acceptance and local control pattern. The study has also shown that over-protectiveness leads to low control center. - There are differences of statistical indications between males and females in the independency pattern in favor of males, and differences between males and females in the protection pattern in favor of females.